A new species of Zorotypus (Insecta, Zoraptera, Zorotypidae) and the earliest known suspicious mating behavior of Zorapterans from the mid‐cretaceous amber of northern Myanmar. (27th March 2019) - Chen, Xinyu; Su, Guifen
Abstract: A new species of the insect order Zoraptera, Zorotypus pusillus, sp. n., is described and illustrated based on two ill‐preserved specimens in mid‐Cretaceous amber from the Hukawng Valley in northern Myanmar. Compared with known extinct zorapterans, the new species possesses eight‐segmented antennae and can be readily distinguished from all other extinct and recent members of the order in the presence of a shallow groove connecting two antennal sockets and by unique spination of the metafemur and metatibia. The earliest known suspicious mating behavior of Zoraptera, the intromittent organ of the fossil zorapterans, the egg, and the earliest known basal plate of the male genitalia are briefly discussed. The genitalia of new species are used as an intromittent organ in the majority of mating patterns among living zorapterans. The mating patterns (a copula is performed by males and females) of the most extant species have been present since at least the mid‐Cretaceous. A shared similar aedeagal structure in the new species and in the most extant species suggests an analogous mating behavior. Abstract : A new species of zorapterans is described and illustrated from Myanmar amber. The earliest known intromittent organ of the fossil zorapterans, the egg, and the earliest known basal plate of the male genitalia had been found. Habitus of the new species illustrated that the mating patterns (a copula is performed by males and females) of the most extant species have been present since at least the mid‐Cretaceous.